Electron Probe Microanalysis of Ni Silicides Using Ni-L X-Ray Lines. (26th October 2016) - Llovet, Xavier; Pinard, Philippe T.; Heikinheimo, Erkki; Louhenkilpi, Seppo; Richter, Silvia
Abstract: We report electron probe microanalysis measurements on nickel silicides, Ni5 Si2, Ni2 Si, Ni3 Si2, and NiSi, which were done in order to investigate anomalies that affect the analysis of such materials by using the Ni L3 -M4, 5 line (L α ). Possible sources of systematic discrepancies between experimental data and theoretical predictions of Ni L3 -M4, 5 k -ratios are examined, and special attention is paid to dependence of the Ni L3 -M4, 5 k -ratios on mass-attenuation coefficients and partial fluorescence yields. Self-absorption X-ray spectra and empirical mass-attenuation coefficients were obtained for the considered materials from X-ray emission spectra and relative X-ray intensity measurements, respectively. It is shown that calculated k -ratios with empirical mass attenuation coefficients and modified partial fluorescence yields give better agreement with experimental data, except at very low accelerating voltages. Alternatively, satisfactory agreement is also achieved by using the Ni L3 -M1 line (Lℓ) instead of the Ni L3 -M4, 5 line.